PERCEPTION OF THE ONLINE LEARNING PROCESS OF SEBELAS MARET UNIVERSITY STUDENTS IN THE COVID-19 PANDEMIC ERA - Lintang Ronggowulan; Anton Subarno; Sutarno Sutarno; Sarjoko Lelono; Hikari Dwi Saputro; Fitria Dewi Kartika (Universitas Sebelas Maret (UNS), 2023)
The impact of pandemic Covid-19 is requires all of humanity to carry out social distancing and maintain a distance. As a result of these restrictions, many sectors are affected. One of the most significantly affected sectors is the education sector. In the learning process in the education sector distance learning is applied with the Online system.This distance learning system has also been implemented at Sebelas Maret University Surakarta (UNS) since March 2020. This study aims to determine the perception of the online learning process of UNS students. The method used in this research is a qualitative descriptive method using purposive sampling (active students who take part in learning at UNS). As for the results of this study, it can be seen that from a total of 13 questions in the online learning perception instrument, 62% of the total questions stated that students had difficulties in online learning and there were 38% of the total questions regarding the ease of online learning. So it can be said that the respondents found it difficult and experienced problems in carrying out online learning at UNS like difficult for me to understand the concept and didn’t have good internet access.